2005
DOI: 10.1103/physrevb.71.201403
|View full text |Cite
|
Sign up to set email alerts
|

Rashba effect at magnetic metal surfaces

Abstract: We give experimental and theoretical evidence of the Rashba effect at the magnetic rare-earth metal surface Gd(0001). The Rashba effect is substantially enhanced and the Rashba parameter changes its sign when a metal-oxide surface layer is formed. The experimental observations are quantitatively described by ab initio calculations that give a detailed account of the near-surface charge density gradients causing the Rashba effect. Since the sign of the Rashba splitting depends on the magnetization direction, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
159
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(181 citation statements)
references
References 18 publications
19
159
0
1
Order By: Relevance
“…This was first recognized in angle-resolved photoemission measurements of the surface states of non-magnetic 5d elements, in particular Au [32,80,81], W [82] and Bi [83]. Investigations of rare-earth surface states, notably of Gd [34] and Tb [42], later revealed clear signatures of coexisting Rashba and exchange coupling in the case of FM metal films in the form of magnetization-dependent asymmetry of the electron band dispersion, similar to that sketched in figure 2c. These studies coincide in showing that a heavy metal interface induces large Rashba splittings of the order of 100 meV and that increasing the asymmetry of the charge distribution at a metal surface leads to an increase of such an effect [34,84,85], in agreement with equation (2.6).…”
Section: (D) Spin-orbit Torques In Ultrathin Metal Filmsmentioning
confidence: 93%
See 2 more Smart Citations
“…This was first recognized in angle-resolved photoemission measurements of the surface states of non-magnetic 5d elements, in particular Au [32,80,81], W [82] and Bi [83]. Investigations of rare-earth surface states, notably of Gd [34] and Tb [42], later revealed clear signatures of coexisting Rashba and exchange coupling in the case of FM metal films in the form of magnetization-dependent asymmetry of the electron band dispersion, similar to that sketched in figure 2c. These studies coincide in showing that a heavy metal interface induces large Rashba splittings of the order of 100 meV and that increasing the asymmetry of the charge distribution at a metal surface leads to an increase of such an effect [34,84,85], in agreement with equation (2.6).…”
Section: (D) Spin-orbit Torques In Ultrathin Metal Filmsmentioning
confidence: 93%
“…Equations (2.1)-(2.3) are relevant not only for quantum well structures in zinc blende semiconductors [21,29,30], but also for (Ga,Mn)As films [18] and metal/semiconductor layers such as Fe/GaAs [31]. In the case of metal surfaces [32,33] and metal layers deposited between asymmetric cubic and amorphous interfaces [19,34], g = b = l = 0, i.e. only the Rashba interaction survives.…”
Section: Spin-orbit Coupling In Materials Lacking Inversion Symmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the breaking of translational symmetry in thin films, many parameters have to be taken into account, such as the thickness and the crystalline orientation of the films. Importantly, Rashba surface states 26,27 can be formed around the Fermi level and they were shown to enhance the spin-flip relaxation rate. 23,28,29 Thin film is a keyword for reducing the size of spintronics devices.…”
Section: Introductionmentioning
confidence: 99%
“…19 For nonmagnetic surfaces, the Rashba field lifts the spin degeneracy of the surface states, 19 whereas for magnetic ones, it leads to an asymmetric shift of the spin nondegenerate bands. 20 Using both experimental and theoretical approaches it was found that indirect exchange interactions between transitional metal ions mediated by oxygen ions of the crystalline lattices play a critical role in formation of the main features in the electronic structure of complex manganites 21,22 in accordance with RKKY mechanism. [23][24][25] The photoemission and X-ray spectroscopy 26,27 revealed antiferromagnetic bonding of the oxygen holes with spin configurations of Mn +3 ions in La 1-x Sr x MnO 3 .…”
Section: Introductionmentioning
confidence: 99%